Bioinspired Platelet-like Nanovector for Enhancing Cancer Therapy via P-Selectin Targeting - Shengli Wan; Yuesong Wu; Qingze Fan; Gang Yang; Haiyang Hu; Singkome Tima; Sawitree Chiampanichayakul; Songyot Anuchapreeda; Jianming Wu (Pharmaceutics, 2022)
Cancer is a major threat to the health of humans. Recently, various natural products including curcumin (CCM) have attracted enormous interest for efficacious cancer therapy. However, natural therapeutic agents still encounter certain challenges such as rapid clearance, low bioavailability, and poor tumor targeting. Recently, the platelet membrane (PM) camouflaged nanoparticle has provided a promising solution for cancer targeting therapy. Nevertheless, only limited efforts have been dedicated to systematically explore the mechanism of affinity between PM bioinspired nanoparticles and various tumor cells. Herein, a CCM-encapsulated platelet membrane biomimetic lipid vesicle (CCM@PL) with a size of 163.2 nm, zeta potential of −31.8 mV and encapsulation efficiency of 93.62% was developed. The values of the area under the concentration-time curve and mean residence time for CCM@PL were 3.08 times and 3.04 times those of CCM, respectively. Furthermore, this PM biomimetic carrier showed an excellent affinity against Huh-7, SK-OV-3 and MDA-MB-231 cell lines due to the biomolecular interaction between P-selectin on the PM and tumoral CD44 receptors. In addition, CCM@PL displayed enhanced cytotoxicity compared with free CCM and the synthetic formulation. Overall, our results suggest that this developed PM biomimetic lipid nanovector has great potential for targeted cancer treatment and natural components delivery.